Objective and Subjective Measures of Child Poverty in Denmark - Hussain, Azhar (Samfundsøkonomen, 2023)
The relative poverty line has been criticized for being arbitrary since it is defined by purely statistical measures without any theory linking objective income poverty to subjectively experienced poverty. The objective-subjective poverty nexus is explored empirically by comparing poverty measures for Danish children using EU-SILC data from 2019. The objective measure is based on the 50 % poverty line, while the subjective measures cover deprivation, financial coping, and accumulation of deprivations. Results shows a far from perfect overlap between objective and subjective poverty, but the subjective poverty risk is much higher for income poor children compared to non-poor children.